The Effect of The Project-Based Learning (PjBL) Model on Students' Cognitive Learning Outcomes: - Weni Rostakina; Ismail Efendi; Sri Nopita Primawati (PAIDAGOGIA: Jurnal Inovasi Pendidikan dan Pembelajaran, 2025)
This study investigates the effect of the Project-Based Learning (PjBL) model on students' cognitive learning outcomes, compared with Problem-Based Learning (PBL), in senior high school biology. The research was motivated by persistently low cognitive achievement and teacher-centred practices observed at SMA Negeri 3 Selong, where many Grade X students scored below the minimum mastery criterion and struggled to construct coherent scientific arguments. A quantitative quasi-experimental design with a non-equivalent control group pretest–posttest design was employed. The population consisted of all Grade X students (N = 84), with purposive sampling used to select two intact classes: X-8 as the experimental group (PjBL; n = 21) and X-7 as the control group (PBL; n = 21). The experimental class engaged in an authentic project constructing aquascapes from recycled jars, while the control class followed PBL-based instruction on the same content. Cognitive learning outcomes (C1–C4) were measured using a multiple-choice and an essay test. Assumption checking using the Shapiro–Wilk and Levene's tests indicated that posttest data met the requirements for parametric analysis. An independent-samples t-test on posttest scores revealed a statistically significant difference between groups (p = 0.001), with the PjBL class outperforming the PBL class by an average of 17.476 points. These findings demonstrate that PjBL has a significant and positive impact on students' cognitive learning outcomes in biology and is more effective than PBL in enhancing lower- and middle-order cognitive processes. The study recommends systematic integration of PjBL in science classrooms and further research with larger, multi-site samples, including additional outcome variables such as motivation, critical thinking, and creativity.